2011
DOI: 10.1083/jcb.201107083
|View full text |Cite
|
Sign up to set email alerts
|

Neuregulin/ErbB regulate neuromuscular junction development by phosphorylation of α-dystrobrevin

Abstract: Neuregulin/ErbB signaling maintains high efficacy of synaptic transmission by stabilizing the postsynaptic apparatus via phosphorylation of α-dystrobrevin1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
76
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 50 publications
2
76
0
Order By: Relevance
“…We also demonstrated that ablation of ERBB2/4 receptors resulted in a lack of phosphorylation of the 75 kDa protein 1 . In addition, the amount of the 75 kDa protein detected on western blots, compared to the 89 kDa protein, was reduced in Erbb2/4 dKO myotubes.…”
Section: Resultsmentioning
confidence: 81%
See 4 more Smart Citations
“…We also demonstrated that ablation of ERBB2/4 receptors resulted in a lack of phosphorylation of the 75 kDa protein 1 . In addition, the amount of the 75 kDa protein detected on western blots, compared to the 89 kDa protein, was reduced in Erbb2/4 dKO myotubes.…”
Section: Resultsmentioning
confidence: 81%
“…We reported previously that on western blots following immunoprecipitation, there were two isoforms of α-dystrobrevin1 associated with DAPC, a 75 kDa and 89 kDa protein 1 . We also demonstrated that ablation of ERBB2/4 receptors resulted in a lack of phosphorylation of the 75 kDa protein 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations